Assédio sexual no ambiente de trabalho e empresas: principais medidas de prevenção, precaução e remediação ao assédio sexual no meio ambiente do trabalho - Anguinoni, Guilherme (Universidade do Vale do Rio dos Sinos, 2024)
Sexual harassment is a delicate issue and can occur in numerous social contexts, with the workplace being one of the most prevalent due to its peculiarities such as the daily time spent there, the proximity between individuals, and the inherent vulnerability of the employee. It is necessary, therefore, to reflect on how it is possible to confront situations of sexual harassment in the workplace. In this context, the question aimed to be answered from this research is: what are the main tools available to companies to fulfill their role in combating sexual harassment in their workplace? Among the hypotheses put forward are employee literacy and awareness regarding sexual harassment, the provision of an anonymous reporting channel, the use of security cameras, and the promotion of manager training in identifying signs of sexual harassment. The general objectives are to establish the main instruments available to companies to face sexual harassment in the workplace, and the development, based on the what was found in the first general objective, of a course/lecture aimed at companies to assist in combating sexual harassment in the workplace and communicating about this issue to employees. This study, which is of an applied research nature, with an exploratory objective and a qualitative approach to the problem, through the literature review method, was divided into four stages, each corresponding to a chapter: delimitation of the phenomenon analyzed based on the definition of the concepts of sexual harassment and workplace environment; identification and examination of the main national and international laws related to sexual harassment, as well as the principles of prevention and precaution; research and interpretation of data to obtain an overview of sexual harassment in Brazil; proposal of the main prevention, precaution, and remediation tools available to companies, and development of a programmatic content for a course/workshop oriented at companies, which serves both as a practical and didactic way to implement these tools, and as a way to encourage the adoption of other measures, such as regular interviews with employees, use of compliance, and promotion of diversity. In the end, it was found that there are other numerous tools available to companies aiming to combat sexual harassment, suitable both for preventing such situations from occurring in the workplace and for remedying and mitigating the damage resulting from such events if they were to occur.
Keywords: Assédio sexual; Meio ambiente de trabalho; Prevenção; Precaução; Sexual harassment; Workplace environment; Prevention; Precaution; ACCNPQ::Ciências Sociais Aplicadas::Direito